Hollywood or history? : an inquiry-based strategy for using film to teach salient social issues in elementary social studies - Pennington, Lisa K.; Fortune, Donna; Tackett, Mary E.; Horst, Paige Hayes; Kessler, Meghan A. (Hollywood or history, 2025)
"Teaching and learning through Hollywood, or commercial, film and television productions is anything but a new approach and has been something of a mainstay in the classroom for nearly a century. However, purposeful and effective instruction through film is not problem-free and there are many challenges that accompany classroom applications of Hollywood motion pictures. In response to the problems and possibilities associated with teaching through film, we are developing a collection of practical, classroom-ready lesson ideas that might bridge gaps between theory and practice and assist teachers endeavoring to make effective use of film in their classrooms. We believe that film can serve as a powerful tool in the social studies classroom and, where appropriately utilized, foster critical thinking and civic mindedness. The NCSS College, Career, and Civic Life (C3) framework, represents a renewed and formalized emphasis on the perennial social studies goals of deep thinking, reading and writing. We believe that as teachers endeavor to digest and implement the platform in schools and classrooms across the country, the desire for access to structured strategies that lead to more active and rigorous investigation in the social studies classroom will grow increasingly acute. Our hope is that this edited book might play a small role in the larger project of supporting practitioners, specifically K-6 teachers of social studies content, by offering a collection of classroom-ready tools based on the Hollywood or History? strategy and designed to foster inquiry through the careful use of selected motion pictures and television productions"--